2011
DOI: 10.1122/1.3593471
|View full text |Cite
|
Sign up to set email alerts
|

Extensional flow-induced crystallization of isotactic poly-1-butene using a filament stretching rheometer

Abstract: A filament stretching rheometer is used to investigate the extensional flow-induced crystallization of two commercial grade isotactic poly-1-butene samples. The degree of crystallinity of the stretched fibers is quantified using differential scanning calorimetry measurements as a function of extension rate and accumulated Hencky strains. All the measurements are performed using the Janeschitz-Kriegel protocol. The samples are first melted to erase their thermal and mechanical history. They are then quickly que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
3
34
1
Order By: Relevance
“…However, for polydisperse systems, shish-kebab morphologies can be generated if the specific work imposed by the flow is large enough to deform the higher molecular weight fractions of the melt (Mykhaylyk et al 2010). This was recently observed in extensional flows by Chellamuthu et al (2011) for a polydisperse poly-1-butene sample that developed a shish-kebab morphology even for extension rates less than one over the Rouse time,ε < 1/λ R .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, for polydisperse systems, shish-kebab morphologies can be generated if the specific work imposed by the flow is large enough to deform the higher molecular weight fractions of the melt (Mykhaylyk et al 2010). This was recently observed in extensional flows by Chellamuthu et al (2011) for a polydisperse poly-1-butene sample that developed a shish-kebab morphology even for extension rates less than one over the Rouse time,ε < 1/λ R .…”
Section: Introductionmentioning
confidence: 92%
“…As a result, the strain requirement for flow-induced crystallization is less in extension than it is in shear (Sentmanat et al 2010). Even though extensional flows are able to generate greater molecular alignment than shear flows (Hadinata et al 2007) and therefore more effectively enhance the resulting crystallization kinetics and morphological changes, very few studies have systematically investigated the effect of pure extensional flows on crystallization (Chellamuthu et al 2011;Hadinata et al 2007;Sentmanat et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Hence, the values reported here are in the order of what is expected. The total heat release decreases with increasing shear rate, from 25 J/g at the lowest shear rate to 18 J/g at the highest shear rate, whereas Chellamuthu et al observed that total crystallinity increased with increasing flow strength (Chellamuthu et al 2011). Possibly, there is some heat leakage into the rotor of the rheometer, which becomes more noticeable at faster crystallization rates.…”
Section: Shear Heatingmentioning
confidence: 89%
“…4a. The heat of fusion of the form II modification of poly(1-butene) was reported to be 58-65 J/g (Alfonso et al 2001), and crystallinity for melt-crystallized poly(1-butene) samples was reported to be in the order of 40 % (Chellamuthu et al 2011;Azzurri 2003). Hence, the values reported here are in the order of what is expected.…”
Section: Shear Heatingmentioning
confidence: 99%
“…Here ̇ is the strain rate applied to the polymer solution, with the coil-stretch transition believed to occur for flows at Wi = 0.5. [72][73][74] The longest relaxation time can be calculated from both Rouse (λ ~ Mw 2 ) and Zimm (λ ~ Mw 1.5 ) models. [75] Both of these models, like Equation (5), point to a decrease in the critical strain rate for coil-stretch transition with an increase in polymer molecular weight.…”
Section: Defined As the Ratio Of Extensional Viscosity (ηE) To Shear mentioning
confidence: 99%